Accessibility Inequality and Income Disparity in Urban China: A Case Study of Guangzhou. Issue 1 (2nd January 2019) - Chen, Zifeng; Yeh, Anthony Gar-On
Abstract : Unlike in Western cities, where the poor population tends to be concentrated in the deprived inner-city areas and experiences low accessibility, the geographic distribution of the low-income population in Chinese cities might be relatively dispersed across accessibility-rich and accessibility-poor areas. This study aims to examine the relationships between income disparity and accessibility inequality in Chinese cities, as well as to identify the particular group of low-income residents who are at risk of inaccessibility. We conducted an empirical study in the city of Guangzhou, China, based on the population census, points of interest, and road network data and measured accessibility based on the three-step floating catchment area (3SFCA) method. Results reveal that although the essential services are significantly concentrated in the central-city areas, the geographic distribution of the low-income population is considerably dispersed across the central-city and suburban areas, thereby indicating the possibility of considerable intragroup inequality of accessibility among the low-income group. The findings from the regression analyses suggest that although urban development in Chinese cities has not resulted in the distinct residential segregation observed in Western cities, the low-income population might still face a dilemma between small floor area and low service accessibility. The study also reveals that nonlocal residents as well as nonurban hukou holders among the low-income population living in suburban areas also experience low service accessibility, which highlights the importance of incorporating hukou as an explanatory variable in analyzing accessibility inequality issues in the Chinese context. Key Words: 3SFCA, inequality, service accessibility, suburbanization, urban China . 不同于西方城市贫穷人口倾向集中于衰败的市中心地区，并经验较低的可及性，中国城市低收入人口的地理分佈，相对而言较为分散，并遍佈可及性高与可及性低的地区。本研究旨在检视中国城市的所得差异与可及性不均之间的关系，并指认面临可及性风险的低所得居民之特定群体。我们根据人口统计、兴趣点与道路网络数据，在中国广州的城市中进行经验研究，并根据三阶段流动搜寻法 (3SFCA) 测量可及性。研究结果显示，尽管基本生活服务显着地集中在城市中心地区，但低收入人口的地理分佈大幅分散在市中心与郊区，因而指出出低收入群体中巨大的群体内部可及性不均的可能性。迴归分析的研究结果显示，尽管中国城市发展尚未导致在西方城市所观察到的显着居住隔离，但低收入人口却仍可能面临小楼地板面积抑或低落的服务可及性之困境。本研究同时揭露，居住于郊区的低收入人口中，非在地居民与非城市户口所有者，同时经历了低落的服务可及性，凸显出分析中国脉络下的可及性不均议题时，纳入户口作为解释变因的重要性。关键词： 3SFCA，不均，服务可及性，郊区化，中国城市。 A diferencia de lo que ocurre en las ciudades occidentales, donde la población pobre tiende a concentrarse en las áreas urbanas más deprimidas y a experimentar mala accesibilidad, la distribución geográfica de la población de bajos ingresos en las ciudades chinas podría darse de manera relativamente dispersa a través de áreas de accesibilidad tanto muy buenas como malas. Este estudio apunta a examinar las relaciones entre disparidad del ingreso y desigualdad de accesibilidad en ciudades chinas, lo mismo que a identificar el grupo particular de residentes de bajos ingresos que se encuentran en riesgo de inaccesibilidad. Llevamos a cabo un estudio experimental en la ciudad china de Guangzhou, apoyado en el censo de población, puntos de interés y datos sobre la red de carreteras y la medida de accesibilidad, con base en el método de área de cuenca flotante de tres etapas (3SFCA). Los resultados revelan que, aunque los servicios esenciales están significativamente concentrados en las áreas de la ciudad central, la distribución geográfica de la población de bajos ingresos es considerablemente dispersa a través de la ciudad central y las áreas suburbanas, indicando así la posibilidad de mucha desigualdad en la accesibilidad a nivel de grupo entre la gente de bajos ingresos. Los hallazgos de los análisis de regresión sugieren que, aunque el desarrollo urbano de las ciudades chinas no ha resultado en la clara segregación residencial que se observa en las ciudades occidentales, la población de bajos ingresos podría enfrentar todavía un dilema entre área de planta muy reducida y bajo servicio de accesibilidad. También revela el estudio que los residentes no locales, lo mismo que los propietarios dentro del sistema hukou no urbano, parte de la población de bajos ingresos que viven en áreas suburbanas, también experimentan baja accesibilidad a los servicios, lo cual destaca la importancia de incorporar el hukou como una variable explicativa para analizar problemas de desigualdad por accesibilidad en el contexto chino. Palabras clave: 3SFCA, accesibilidad a los servicios, China urbana, desigualdad, suburbanización .